A mídia e o jazz no Brasil: investigação em torno da recepção crítica dos festivais de jazz na imprensa paulistana - Amaral, Luiza Spínola (2011)
The main objective of this research is to rescue the historical memoire of brazilian popular music through the media coverage that jazz festivals get from São Paulo's press. It's also about focusing on the relationship between the cultural industry and the critics, exposing how our musical memory is smothered by a certain sociological view of jazz as just another product of american culture and how this line of opinion, suspicious as it is, counterpoints the semiotic stream of critics that, among other musicologists, belongs Augusto de Campos. It's a documental and bibliographical research. The core of the research is a gathering of journalistic stories exposed here, establishing an analytical overview of São Paulo's press media